Electromagneto-mechanical model of high temperature superconductor insert magnets in ultra high magnetic fields. (1st May 2022) - Trillaud, Frederic; Berrospe-Juarez, Edgar; Zermeño, Víctor M R; Grilli, Francesco
Abstract: Second-generation high-temperature superconducting (2G HTS) tapes are considered to be the main candidates for the development of future ultra-high DC magnetic field magnets. In such applications, the usability of the HTS magnets can be strongly impaired by large screening currents developed in the flat strip of the tapes. These currents lead to the generation of a screening current-induced field (SCIF) that can deteriorate the performance by affecting the stability and the homogeneity of the magnetic field. Besides the SCIF, there is also the likely mechanical degradation of the tapes under the action of large Lorentz forces. The mechanical degradation and the presence of large screening currents intertwine to affect the reliable operation of 2G HTS magnets. To study the combined issues, an electromagneto-mechanical model based on tensile mechanical characterization of short samples was built to simulate the coupled electromagnetic and mechanical behaviors of insert magnets made of 2G HTS tapes under very high magnetic field. The coupling is carried out by considering the dependence of the n index and the critical current density J c on the local relative deformation in addition to the magnetic flux density. The case study is the Little Big Coil (LBC, version 3) which broke the world record of the strongest continuous magnetic field achieved to this date. An analysis of the electromagneto-mechanical behavior of the LBC is conducted on the basis of information extracted from the literature to show that the proposed model can assess the current magnitude at which the insert magnet quenched. Additionally, it is shown that the model can also provide some insights on the impact of the mechanical degradation of the tape on the SCIF hysteresis loop. The studies are conducted on the original LBC and on versions that include additional modifications such as harnessing and co-winding with rigid metallic tapes. These modifications are employed to limit the mechanical degradation of the HTS insert magnet under ultra-high magnetic field. They are expected to deliver an extra safety margin to 2G HTS insert magnets.